ANALYSIS OF THE DIFFICULTY OF EXAM QUESTIONS AT STATE JUNIOR HIGH SCHOOL - Neli Agustin; Septi Utari Putri; Rafikan Aria Ganda; Ahmad Walid (Science Education, Institut Agama Islam Negeri Ponorogo, 2022)
The study aims to analyze level of difficulty of the exam questions for Class VII and VIII at junior high school Negeri 05 Bengkulu City. This study used a qualitative descriptive research design. The instrument used in this study was the text of the science exam questions for junior high school and equivalent. Higher order thinking skills are not only formed in the cognitive aspect but are able to improve the skills and effective aspects of students. One of them is the collected data is analyzed using the Difficulty Index formula. Data analysis used descriptive percentage. Calculate the individual value of each student in class VIII A of junior high school Negeri 05 Bengkulu City. The results showed that the analysis of the difficulty level of science exam questions for class VIII and VII Junior high schools Negeri 05 Bengkulu City for the 2020/2021 academic year had a difficult question category in class VII of only 30%, the easy question category was 70%, as well as class VIII. difficult category questions,30% of easy category questions, 30% moderate questions 40%. This shows that the quality of the exam questions is very good. A good measuring instrument test will produce good data, the teacher can know the student's ability correctly if the measuring instrument used is a good measuring instrument. Questions have very good/very good discriminating power. Matter of material, construction and some parts of the language need to be improved. Data collection tools used are through note takers and interview guides.